Designing a Web-Based E-Counseling Application using the Biopsychosocial Balance Theory to Optimize Academic Guidance and Counseling Services (Case Study: Darussalam Gontor University) - Widya Kurniawan; Aziz Musthofa; safitri, Ayu Caesar (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Academic guidance and counseling services play an important role in supporting student welfare and academic success. However, the implementation of counseling services at Darussalam Gontor University still faces various obstacles, such as an unstructured scheduling process, manual counseling history recording, and limited access to services for students. This study aims to design and develop a web-based e-counseling application using biopsychosocial balance theory to optimize academic guidance and counseling services at Darussalam Gontor University.The research method used is the System Development Life Cycle (SDLC) with a Waterfall approach, which includes the stages of needs analysis, system design, implementation, testing, and maintenance. The developed application provides features for making counseling appointments, selecting counselors, filling out counseling forms based on biological, psychological, social, and spiritual aspects, and confirmation of counseling schedules by counselors. System testing was conducted using Black Box Testing to ensure that all system functions ran according to user needs. The results of the study show that the e-counseling application that was developed works well and meets the needs of users, including students, counselors, and administrators. With this application, the counseling service process has become more structured, efficient, and accessible. It is hoped that this e-counseling application can become a digital solution that supports the improvement of the quality of academic guidance and counseling services at Darussalam Gontor University.